The effect of economic crisis and targeted motorcycle safety program on traffic deaths in Malaysia - Law, T. H.; Radin Umar, R. S. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/